Philosophy of grammatical person(s) in Erté’s work - Markov Alexander Viktorovich; Shtayn Oksana Aleksandrovna (Studia Humanitatis)
The greatest designer Erté combined the unpredictable revitalization of ornament and the literalization of sensuality, the subordination of feelings to the paradigmatic plan of expressiveness. This allowed Roland Barthes to give a convincing semiotic interpretation of the artistэs work in 1975. In the same year Erté released his autobiography, where he presented the dialogical origins of his work. The paper points out the common sides of the artist’s autoreflection and the philosopher’s reflection on his work, and concludes on the significance of the distinction of the first, second and third person of the dialog for Erté's auto-communicating artistic programs and for the semiology of late Barthes.